Remnants of Early Carboniferous I-type granodiorite plutons in the Bavarian Forest and their bearing on the tectonic interpretation of the south-western sector of the Bohemian Massif (Bavarian Zone) - Finger,F.; Dunkley,D.J.; Rene,M. (Journal of Geosciences, 2010)
The Bavarian Zone of the south-western Bohemian Massif is a late Variscan high heat-flow region, characterized by numerous granite intrusions and large amounts of LP-HT anatectic rocks, the latter comprising meta- and diatexites derived from sedimentary and igneous protoliths. Imaging and SIMS U-Pb dating of zircon from a distinctive type of hornblende-bearing diatexite, with a presumed igneous protolith, was done to gather information on both metamorphism and pre-anatectic crustal evolution. Zircon crystals have two phases of growth zoning, with oscillatory-zoned grains (visible through cathodoluminescence, CL, imaging) modified and surrounded by relatively uniform, high luminosity zircon. Analyses on oscillatory-zoned zircon yield an age of 344 ± 2 Ma (2σ), interpreted as the formation age of the igneous protolith. More luminescent overgrowths, interpreted as having formed during anatexis, were dated at 323 ± 3 Ma. Based on these dates, and on geochemical similarities, the protolith can be perfectly correlated with the high-K calc-alkaline Blatna suite of the Central Bohemian Plutonic Complex, c. 70 km to the north. This correlation strengthens tectonic models interpreting the Bavarian Zone as a reheated but integral constituent of the Variscan collisional crust of the Bohemian Massif, as opposed to an independent basement terrane assembled by late-Variscan orogenesis.
Keywords: Variscan orogen; Bohemian Massif; Bavarian Zone; Granodiorite; Zircon; U-Pb dating